MicroRNA-27b Enhances the Hepatic Regenerative Properties of Adipose-Derived Mesenchymal Stem Cells - Kuang-Den Chen; Kuang-Tzu Huang; Chih-Che Lin; Wei-Teng Weng; Li-Wen Hsu; Shigeru Goto; Toshiaki Nakano; Chia-Yun Lai; Chao-Pin Kung; King-Wah Chiu; Chih-Chi Wang; Yu-Fan Cheng; et al. (Elsevier, 2016)
Adipose-derived mesenchymal stem cells (ASCs) are readily available multipotent mesenchymal progenitor cells and have become an attractive therapeutic tool for regenerative medicine. We herein investigated the mechanistic role of how miR-27b modulated regenerative capacities of ASCs. Intravenous administration of miR-27b-transfected ASCs (ASCs-miR-27b) was conducted after 70% partial hepatectomy (PH). After PH, rats injected with ASCs-miR-27b had decreased inflammatory cytokines and increased hepatocyte growth factor and other related growth factors. We showed that the nature of ASCs-miR-27b to inhibit hepatic stellate cell activation was dependent upon peroxisome proliferator-activated receptor gamma coactivator-1 alpha (PGC-1α) in vitro. Moreover, expression of miR-27b in ASCs induced heme oxygenase-1 (HO-1), resulting in increased production of ATP, protective cytokines/growth factors, and genes involved in mitochondrial biogenesis in a PGC-1α-dependent manner. RNA sequencing (RNA-Seq) analysis revealed drastic transcriptional changes in livers treated with ASCs-miR-27b after PH. The differentially expressed genes classified into "regeneration," "fibrosis," and "mitochondrial biogenesis" clusters were mainly mitochondrial. The potential biological context reflecting the effects of PGC-1α by ASCs-miR-27b treatment was also observed by the subnetwork analysis with HO-1 and PGC-1α being the top-ranked regulatory genes. We demonstrate autologous ASCs-miR-27b enhances liver regeneration and, importantly, preserves hepatic function through paracrine actions which offers a viable therapeutic option to facilitate rapid recovery after liver injury.